A study of the hydraulically interconnected inerter-spring-damper suspension system. Issue 4 (2nd October 2017) - Wang, Ruochen; Ye, Qing; Sun, Zeyu; Zhou, Weiqi; Cao, Yichuan; Chen, Long
ABSTRACT: A new hydraulically interconnected inerter-spring-damper suspension (HIISDS) is developed to compensate for traditional passive suspension limitations, such as the imbalance of ride performance and handling stability. In this article, the structure and mechanism of the HIISDS system is briefly introduced at first, and compiled with hydraulically interconnected suspension (HIS) mode and hydraulic inerter-spring-damper (ISD) suspension mode. A vehicle dynamic model of HIISDS system is then derived through these two suspension modes by using Matlab/Simulink. Two different road excitations are used to validate the adaption of the two suspension modes. The effectiveness of HIISDS has been verified by simulation results, in which vehicle ride comfort and handling stability are effectively coordinated through the HIISDS model switch. Finally, an HIISDS suspension prototype is designed based on Simulink results, and test results reconfirm the partial performances of HIISDS modes effectively.